Innovex enteprise : Portable cycle cooker/ Muhammad Faiz Mohamad ... [et al.] - Mohamad, Muhammad Faiz; Ahmad, Muhammad Arif; Raja Alang Muhammad, Muhammad Aiman; Muhammad, Ahmad Fikri; Hashim, Muhammad Haziq (2018)
INNOVEX Enterprise produces a portable cycle cooker that combine four types of cooking method which are grilling, steaming, boiling and frying. Our company tagline is "Go Anywhere, Cook Anywhere ". Our business will be located at Jalan Cenderai 27, Taman Kawasan Perindustrian Kata Putri, Masai, Johar. Our company are focusing on producing this portable cycle cooker for the Malaysian. As a local company, we hope that this company can be the largest market share holder in this cookware industry.